Identifikasi Jamur Patogen Pada Air Bak Toilet Masjid Kecamatan Arosbaya Kabupaten Bangkalan - Dwi Aprilia Anggraini; Norma Farizah Fahmi; Kamal Musthofa (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Toilet tub water is one source of disease transmission. Many waterborne diseases are caused by contamination with bacteria, viruses, parasites, and fungi. Contamination in tub water by fungi comes from toilet tub feces and turbidity in water that is not cleaned. The purpose of this study was to determine the pathogenic fungi found in mosque toilet water. Laboratory tests included implanting on PDA (Potato dextrose agar) media using pour plates. Identification was made macroscopically by looking at the shape and color of the colonies, and microscopically using LCB solution. The results obtained from this study were found in the fungi Candida albicans, Aspergillus, Trichophyton, Penicillium, and Rhizopus in mosque toilet tub water in Arosbaya District, Bangkalan City, found the presence of pathogenic fungi.